Growth and characteristics of p-type doped GaAs nanowire *Project supported by the National Natural Science Foundation of China (Nos. 61376019, 61504010, 61774021) and the Fund of State Key Laboratory of Information Photonics and Optical Communications (Beijing University of Posts and Telecommunications), China (Nos. IPOC2017ZT02, IPOC2017ZZ01). (May 2018) - Li, Bang; Yan, Xin; Zhang, Xia; Ren, Xiaomin
Abstract: The growth of p-type GaAs nanowires (NWs) on GaAs (111) B substrates by metal-organic chemical vapor deposition (MOCVD) has been systematically investigated as a function of diethyl zinc (DEZn) flow. The growth rate of GaAs NWs was slightly improved by Zn-doping and kink is observed under high DEZn flow. In addition, the I – V curves of GaAs NWs has been measured and the p-type dope concentration under the II/III ratio of 0.013 and 0.038 approximated to 10 19 –10 20 cm −3 .